Meningkatkan Efektivitas Pembelajaran Seni Tari Siswa Kelas V SD melalui Ensiklopedia Digital - Firman Ardiyanto; Atip Nurharini (Jurnal Pendidikan dan Pengajaran, 2024)
The modern era of education demands digitalization in the teaching and learning process. Learning without using digital media that suits the participants' characteristics impacts arts learning outcomes at a low rate. This research aims to develop a digital encyclopedia of dance learning for fifth-grade elementary school students. This research method is Research & Development (R&D) with the ADDIE model. The research subjects consisted of 2 experts, 1 teacher and 26 students. Data collection techniques were observation, interviews, questionnaires and written tests. Quantitative and qualitative descriptive data analysis techniques. The research results show that the digital encyclopedia received 83.75% validity from material experts and 96% from media experts, which is a very feasible category. The digital encyclopedia was assessed as practical, with 95% of students being teachers, 91% being small group students, and 94% being large group students in the very good category. The effectiveness of digital encyclopedias in learning activities is proven by increasing the average learning outcomes of students with an N-Gain value of 0.6490. It can be concluded that the digital encyclopedia has criteria for feasibility, practicality and effectiveness in learning dance in grade V elementary school. This research implies that the digital encyclopedia of dance can be used by elementary school teachers in dance learning activities.